Preparation and application of polyester based on coumestrol and insulating heat-resistant material
Coumar estrol was reacted with methyl 3-bromomethylbenzoate to obtain diester monomer M and was condensed and polymerized with other compounds to prepare a polyester based on coumar estrol. The polyester and nano-silica blended and extruded granulation solve the problem of degradation of the insulation performance of the polyester material in high temperature environments and achieves efficient improvement of insulation heat resistance.
Patent Information
- Application Number
- CN202311052738.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
AI Technical Summary
The insulation performance of existing polyester materials in high temperature environments has decreased, making it difficult to meet the application needs of electrical equipment under high temperature conditions.
Coumar estrus and methyl 3-bromomethylbenzoate were used to react coumar estrus to obtain diester monomer M, and melt-condensation polymerization with dimethyl 1,4-cyclohexadiasterate and ethylene glycol dihydroxymethyl ether to obtain Polyester based on coumar estrus. The polyester and nano-silica were then blended and extruded to granulate to prepare an insulating heat-resistant material with excellent performance.
It improves the insulation performance and heat resistance of polyester materials, and enhances its stability and application potential in high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the synthesis of polyester based on coumestrol and the preparation and application of insulating heat-resistant materials, and belongs to the field of polymer synthesis and composite materials. Coumestrol is used as a raw material to carry out hydroxy esterification reaction with 3-bromomethylbenzoic acid methyl ester to obtain a diester monomer M, and the monomer M is melt-condensed with 1,4-cyclohexanedicarboxylic acid dimethyl ester and ethylene glycol dihydroxymethyl ether in a certain proportion to obtain a polyester. On this basis, further processing can be used to prepare an insulating heat-resistant material with excellent performance. Background Art
[0002] With the continuous development of my country's power resources, the corresponding electrical equipment safety requirements also need to be improved. The reduction of equipment insulation performance is likely to cause power system accidents, so it is also crucial to improve the insulation performance of the corresponding materials. Polymer materials, as electrical insulation materials, occupy an important position in electrical equipment. Polyester materials are often used as important insulating parts in composite materials to meet the insulation, heat resistance and aging resistance of composite materials. [1] . ([1] Huang Shihao. Research on insulation aging characteristics of polymer film materials under the action of complex factors [D]. Tianjin University, 2018.]). With the development of materials science and the improvement of electrical equipment requirements, dielectric materials must not only meet the conventional mechanical performance requirements, but also the insulation performance requirements. Therefore, improving the insulation performance of polyester materials can broaden the application market of polyester materials.
[0003] Biaxially oriented polyester film has good thermodynamic properties and is used in various packaging applications. It is also gradually being used in modern industrial fields such as electronics, optics, and imaging. However, polyester film materials still have some defects. For example, as an electrical insulating material, its heat resistance is low, and its application and development are limited. The PET currently used in the market has certain defects in heat resistance. The products produced will produce irreversible deformation at high temperatures, which limits the application of polyester in the electronics industry, automotive industry, electrical equipment and other fields. [2]. ([2] Lin Yanyan, Huang Wenguang, Liu Yumin, et al. Research on the heat resistance of modified copolyester PETG [J]. Polyester Industry, 2022, 35(3): 27-29.) In addition to PET, PBT is another polyester material widely used in the market with excellent comprehensive performance, but its notched impact strength is low and its heat deformation temperature is low, which also limits its application in high temperature environments. Many electrical equipment will inevitably be accompanied by an increase in their operating temperature during operation, so the heat resistance of electrical insulation materials is required to be higher, that is, the use temperature of the material must be increased while ensuring insulation, so that it can work normally in a high temperature environment. With the development of science and technology, high heat-resistant electrical insulation polyester film will be widely used in the electronics industry, electrical insulation, circuit printing and other aspects, and the application of polyester will become more and more extensive. Therefore, improving the insulation performance and heat resistance of polyester is very meaningful for the application and development of polyester.
[0004] At present, there are many kinds of heat-resistant materials and insulating materials, among which polyester materials have the characteristics of good mechanical properties, chemical resistance, and excellent electrical properties. However, high temperature conditions have a great influence on the electrical properties of polyester. Materials with both high temperature resistance and good insulation properties can be well applied in electrical, electronic, and communication industries, but there are few polyester materials that meet both heat resistance and insulation properties. Therefore, the development of such materials is very meaningful and valuable. Polyester is blended with a certain proportion of high resistivity materials or materials with excellent thermodynamic properties, which can improve the electrical insulation properties or thermodynamic properties of the material to a certain extent. In recent years, more and more research has been conducted on the theory of nano-dielectrics. With the continuous development of nanotechnology, the application of nano-materials has become more and more extensive. Nano-inorganic materials usually have the advantages of good thermal stability, high temperature resistance, electrical insulation properties, and corrosion resistance. After the polyester matrix is mixed with nano-materials, the nano-materials have high surface activity and cross-link with the matrix polymer chain to reduce the damage of the material to the impact force. At the same time, stress concentration occurs on the surface under the action of external force. Nano-particles can reduce the formation of local discharge or electrical dendrites and thus improve its electrical insulation. The electrical, thermal, and mechanical properties of the composite material formed by the polyester matrix and nano-particles can be further improved. Li Weiguo [3]([3] Li Weiguo, Zhang Nuan, Yang Yaqi. Research progress on electrical insulation properties of epoxy nanocomposite[J].Science Technology and Engineering,2019,19(2) : 11-18) The reported nano-silica / epoxy resin composite material increased the storage modulus, glass transition temperature and dielectric strength by 1241%, 14% and 73% respectively compared with pure epoxy resin, and its dielectric constant decreased from 3.1 of pure epoxy resin to 2.73. Therefore, the blending of polyester and nanoparticles to form a composite material is very meaningful for improving the comprehensive performance of the material.
[0005] The invention prepares an insulating heat-resistant composite material. Coumestrol-based polyester and nano-silicon dioxide are blended, extruded and granulated to obtain a composite material with excellent electrical properties, insulation, heat resistance and mechanical properties. The composite material can be used as a substrate for insulating layers of electrical equipment, circuit boards, cables and the like. Summary of the invention
[0006] In view of these current situations and problems, the present invention aims to provide a method for preparing a polyester and an insulating heat-resistant material based on coumestrol, which specifically involves reacting coumestrol as a raw material with 3-bromomethylbenzoic acid methyl ester to obtain a diester monomer M, and melt-condensing the monomer M with 1,4-cyclohexanedicarboxylic acid dimethyl ester and ethylene glycol dihydroxymethyl ether in a certain proportion to obtain a polyester. Further processing on this basis can prepare a base material for an insulating heat-resistant material with excellent performance.
[0007] In order to achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows: In order to realize the technical solution of the present invention, the present invention discloses a preparation method and use of a polyester based on coumestrol, and the steps of preparing the polyester are as follows: 1. A polyester P based on coumestrol, characterized in that the structure is as shown in Formula I:
[0008] Wherein: in formula Ⅰ, m is 50~60, and n is 62~78.
[0009] 2. A method for preparing a polyester P based on coumestrol, characterized in that the preparation comprises the following steps: (1) Synthesis of diester monomer M: Under N2 protection, 3,9-dihydroxy-6H-benzofurano (3,2-c) furan-6-one with CAS No. 479-13-0 and 3-bromomethylbenzoic acid methyl ester were added into a reactor at a molar ratio of 1: (2-2.2), N,N-dimethylformamide was added to dissolve it, and then potassium carbonate 0.5-0.6 times the molar amount of 3-bromomethylbenzoic acid methyl ester was added. The reaction mixture was then heated to 80-90°C and stirred for 1-3 hours. The filtered solid was washed with distilled water until neutral, recrystallized with chloroform, and dried in an oven at 50°C for 1-2 hours to obtain a diester monomer M having a structure as shown in Formula II:
[0010] (2) Synthesis of polyester crude product: Under nitrogen protection, the structure of the polyester prepared in (1) is The diester monomer M, dimethyl 1,4-cyclohexanedicarboxylate with CAS number 94-60-0 and ethylene glycol dihydroxymethyl ether with CAS number 3586-55-8 are added into a reaction container in a certain proportion, and a certain mass of catalyst is added. The mixture is stirred and reacted at a temperature of 200-220° C. and in a N2 atmosphere for 2 hours. After that, the vacuum degree of the reaction system is controlled at 100-150 Pa and a temperature of 340-355° C. to carry out a condensation reaction for 1-2 hours to obtain a crude polyester.
[0011] (3) Purification of polyester: Dissolve the crude polyester with chloroform, filter out the insoluble matter, add methanol to the clear solution until the precipitate no longer increases, wash the filtered precipitate 2 to 3 times with cooled methanol, filter again and dry the obtained solid at 50 °C for 1 to 2 h to obtain the desired coumestrol-based polyester P.
[0012] 3. Preparation of coumestrol-based polyester, characterized in that: the catalyst described in step (2) is one of tin (II)-ethylhexanoate, dibutyltin (II) oxide, titanium (IV) isopropanol, and potassium fluorotitanate (IV), and the amount of the catalyst used is 0.1% to 0.3% of the mass of the diester monomer M in (1).
[0013] 4. A method for preparing a polyester based on coumestrol, characterized in that the molar ratio of the diester monomer to dimethyl 1,4-cyclohexanedicarboxylate and ethylene glycol dihydroxymethyl ether in step (2) is 1.2: (1-1.1): (2.0-2.4).
[0014] 5. The polyester P obtained by the preparation method of the polyester based on coumestrol is used to prepare an insulating heat-resistant base material. The preparation method comprises the following steps: 92 parts by weight of the polyester P based on coumestrol prepared in step 2, 5 parts by weight of nano-SiO2 with a particle size of 100 nm, 1 part by weight of an antioxidant JY-626 and 2 parts by weight of a polycarbodiimide anti-hydrolysis agent are put into a high-speed mixer and blended evenly, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material.
[0015] Beneficial effects.
[0016] The coumestrol-based polyester prepared by the present invention adopts a melt polycondensation method, has a simple preparation process, is easy to control reaction conditions, has a simple synthesis process, and uses environmentally friendly raw materials.
[0017] Wang, J.G. [4] ([4]Wang, JG; Zhang, XQ; Shen, A.; Zhu, J.; Song,PA; Wang, H.; Liu, XQ Synthesis and properties investigation of thiophene-aromatic polyesters: potential alternatives for the 2,5-furandicarboxylic acid-based ones. Chinese J. Polymer. Science) reported a polyester material PETH with a number average molecular weight M n 3.9×10 4 g / mol, molecular weight distribution coefficient PDI is 1.54, melting point is 192.5°C, tensile strength is 67 MPa, tensile modulus is 1800 MPa, and elongation at break is 378%. Estradiol Polyester P The number average molecular weight is 6.7×10 4 ~7.8×10 4 g / mol, the molecular weight distribution coefficient PDI is 1.78-1.84, the melting point is 307.5-336.5°C, the tensile strength is 95.7-103.6 MPa, the tensile modulus is 2480-2630 MPa, and the elongation at break is 468.6%-496.9%. The mechanical properties of the coumestrol-based polyester P prepared by the present invention are significantly enhanced.
[0018] Zhao Yushun [5]([5]ZHANG S, CHEN WJ, ZHAO YS, et a1. Designing multi-aromaticring epoxy composites to integrate high insulation and high heat resistance performances by electron-induced effect[J]Composites Part B: Engineering, 2022, 243: 1 10107.) reported a composite material with high heat resistance and insulation, and its glass transition temperature and thermal decomposition temperature T d(10%) The breakdown strength is 39.18 kV / mm, the dielectric constant is 3.37, and the dielectric loss is 0.0035. The glass transition temperature of the polyester P based on coumestrol prepared by the present invention is 267.3~272.5℃, and the thermal decomposition temperature T d(10%) The temperature of the polyester P prepared by the present invention is 482-507°C, the melting point is 307.5-336.5°C, the breakdown strength is 64.62-65.48 kV / mm, the dielectric constant is 2.4-2.7, and the dielectric loss is 0.0012-0.0017. In contrast, the polyester P based on coumestrol prepared by the present invention exhibits good heat resistance and insulation.
[0019] Specific implementation cases.
[0020] In order to further illustrate the specific situation of the present invention, the present invention is further elaborated below in conjunction with specific embodiments, but the present invention is not limited to the embodiments, and the required raw materials are all drugs commonly sold on the market.
[0021] Molecular weight test in progress: Gel permeation chromatography test was performed using a Waters GPC instrument (Waters 410), the eluent was chromatography grade chloroform, and the standard solution was a polystyrene solution.
[0022] Mechanical properties test during implementation: The tensile test of the sample test strip was carried out according to the standard requirements of GB / T1040.2-2006, with a tensile rate of 20 mm / min. The elongation at break test was carried out according to the standard requirements of GB / T1040.3-2006.
[0023] Thermal stability test during implementation: DSC test was conducted using TA Q2000 instrument, and the test method was: in a nitrogen atmosphere, the temperature was raised from 30 to 500°C at 10°C / min, maintained at 500°C for 10 minutes, dropped to 30°C at 10°C / min, and then raised to 500°C at the same rate. Thermogravimetric analysis (TGA) test was conducted using Perkin-Elmer (Pyris 1 TGA) instrument, the sample type was polyester powder, and the test method was: in a nitrogen atmosphere, the temperature was kept at 100°C for 10 minutes, and the temperature was raised from 100°C to 800°C at 10°C / min.
[0024] Electrical insulation performance test during implementation: The dielectric constant and dielectric loss of the sample were measured using the YG9100 anti-interference dielectric loss tester. The sample was measured at least 10 times under a test voltage of 2 kV, and the dielectric constant and dielectric loss results were averaged. The breakdown strength of the sample was tested using a RZ2116B voltage breakdown tester.
[0025] Example 1.
[0026] Synthesis of diester monomer M1: Under N2 protection, 5.364g (0.02mol) of coumestrol and 9.163g (0.04mol) of methyl 3-bromomethylbenzoate were added to a 100mL round-bottom flask, and 30mL of N,N-dimethylformamide was added as the reaction solvent. The mixture was stirred with a magnetic stirrer to dissolve it. Then 2.764g of potassium carbonate was added. The reaction mixture was heated to 80°C and stirred for 2 hours. The filtered solid was washed with distilled water until it was neutral, recrystallized with chloroform, and dried in an oven at 50°C for 1 h to obtain diester monomer M1: 9.732g, with a yield of 86.19%.
[0027] Under nitrogen protection, 6.775g (0.012mol) of diester monomer M1, 2.002g (0.01mol) of dimethyl 1,4-cyclohexanedicarboxylate, and 1.802g (0.02mol) of ethylene glycol dihydroxymethyl ether were added to a reaction vessel, and 0.0068g of tin (II)-ethylhexanoate was added. The mixture was stirred at 200°C and N2 atmosphere for 2 hours, and then the vacuum degree of the reaction system was controlled to be 100Pa and the temperature was 340°C for polycondensation reaction for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform, the insoluble matter was filtered out, and sufficient methanol was added to the clear liquid until the precipitation no longer increased. The filtered precipitate was washed 3 times with cooled methanol, and the obtained solid was dried at 50°C for 2 hours after filtering again to obtain polyester P1: 9.114g, with a yield of 86.15%.
[0028] The polyester P1 obtained by the preparation method of the polyester based on coumestrol is used as a base material for preparing an insulating heat-resistant material. The preparation method comprises the following steps: 92 parts by mass of the polyester P1 based on coumestrol, 5 parts by mass of nano-SiO2 with a particle size of 100 nm, 1 part by mass of an antioxidant JY-626 and 2 parts by mass of a polycarbodiimide anti-hydrolysis agent are put into a high-mixer for uniform blending, and then extruded and granulated by an extrusion granulator to obtain a base material for preparing an insulating heat-resistant material. The polyester composite material is processed into a 30 μm polyester composite material by a blow molding process, and the electrical insulation performance, heat resistance, mechanical properties and thermal stability of the polyester composite material are tested (the results are shown in Tables 1 and 2 below). The prepared polyester composite material can be used for the protection of electronic component housings.
[0029] Example 2.
[0030] Synthesis of diester monomer M2: Under N2 protection, 5.364g (0.02mol) of coumestrol and 9.346g (0.0408mol) of methyl 3-bromomethylbenzoate were added to a 100mL round-bottom flask, and 30mL of N,N-dimethylformamide was added as the reaction solvent. The mixture was stirred with a magnetic stirrer to dissolve it. Then 3.383g of potassium carbonate was added. The reaction mixture was heated to 85°C and stirred for 1 hour. The filtered solid was washed with distilled water until it was neutral. After recrystallization with chloroform, it was dried in an oven at 50°C for 2 h to obtain diester monomer M2: 9.662 with a yield of 85.57%.
[0031] Under nitrogen protection, 6.775g (0.012mol) of diester monomer M2, 2.002g (0.01mol) of dimethyl 1,4-cyclohexanedicarboxylate, and 1.983g (0.022mol) of ethylene glycol dihydroxymethyl ether were added to a reaction vessel, and 0.0136g of dibutyltin (II) oxide was added. The reaction was stirred at 210°C and N2 atmosphere for 2 hours, and then the vacuum degree of the reaction system was controlled to be 110Pa and the temperature was 355°C for 1 hour to carry out polycondensation reaction to obtain a crude polyester. The crude polyester was dissolved in chloroform, the insoluble matter was filtered out, and sufficient methanol was added to the clear liquid until the precipitation no longer increased. The filtered precipitate was washed 3 times with cooled methanol, and the obtained solid was dried at 50°C for 1h after filtering again to obtain polyester P2: 9.571g, with a yield of 88.95%.
[0032] The polyester P2 obtained by the preparation method of the polyester based on coumestrol is used as the base material for preparing the insulating heat-resistant material. The preparation method comprises the following steps: 92 parts by weight of the polyester P2 based on coumestrol, 5 parts by weight of nano-SiO2 with a particle size of 100 nm, 1 part by weight of the antioxidant JY-626 and 2 parts by weight of the polycarbodiimide anti-hydrolysis agent are put into a high-mixer for uniform blending, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material. The polyester composite material is processed into a 35 μm polyester composite material by a blow molding process, and the electrical insulation performance, heat resistance, mechanical properties and thermal stability of the polyester composite material are tested (the results are shown in Tables 1 and 2 below). The prepared polyester composite material can be used for wire and cable coating.
[0033] Example 3.
[0034] Synthesis of diester monomer M3: Under N2 protection, 5.364g (0.02mol) of coumestrol and 9.529g (0.0416mol) of methyl 3-bromomethylbenzoate were added to a 100mL round-bottom flask, and 30mL of N,N-dimethylformamide was added as the reaction solvent. The mixture was stirred with a magnetic stirrer to dissolve it. Then, 2.875g of potassium carbonate was added. The reaction mixture was heated to 90°C and stirred for 3 hours. The filtered solid was washed with distilled water until it was neutral. After recrystallization with chloroform, it was dried in an oven at 50°C for 2 h to obtain diester monomer M3: 9.583g, with a yield of 84.87%.
[0035] Under nitrogen protection, 6.775g (0.012mol) of diester monomer M3, 2.002g (0.01mol) of dimethyl 1,4-cyclohexanedicarboxylate, and 2.163g (0.024mol) of ethylene glycol dihydroxymethyl ether were added to a reaction vessel, and 0.0203g of titanium (IV) isopropanol was added. The reaction was stirred at 220°C and N2 atmosphere for 2 hours, and then the vacuum degree of the reaction system was controlled to be 120Pa and the temperature was 350°C for polycondensation reaction for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform, the insoluble matter was filtered out, and sufficient methanol was added to the clear liquid until the precipitation no longer increased. The filtered precipitate was washed twice with cooled methanol, and the obtained solid was dried at 50°C for 2 hours after filtering again to obtain polyester P3: 9.596g, with a yield of 87.71%.
[0036] The polyester P3 obtained by the preparation method of the polyester based on coumestrol is used as the base material for preparing the insulating heat-resistant material. The preparation method comprises the following steps: 92 parts by weight of the polyester P3 based on coumestrol, 5 parts by weight of nano-SiO2 with a particle size of 100 nm, 1 part by weight of the antioxidant JY-626 and 2 parts by weight of the polycarbodiimide anti-hydrolysis agent are put into a high-mixer for uniform blending, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material. The polyester composite material is processed into a 40 μm polyester composite material by a blow molding process, and the electrical insulation performance, heat resistance, mechanical properties and thermal stability of the polyester composite material are tested (the results are shown in Tables 1 and 2 below). The prepared polyester composite material can be used for the housing of electronic component packaging materials.
[0037] Example 4.
[0038] Synthesis of diester monomer M4: Under N2 protection, 5.364g (0.02mol) of coumestrol and 9.713g (0.0424mol) of methyl 3-bromomethylbenzoate were added to a 100mL round-bottom flask, and 30mL of N,N-dimethylformamide was added as the reaction solvent. The mixture was stirred with a magnetic stirrer to dissolve it. Then 3.516g of potassium carbonate was added. The reaction mixture was heated to 80°C and stirred for 1 hour. The filtered solid was washed with distilled water until it was neutral. After recrystallization with chloroform, it was dried in an oven at 50°C for 1h to obtain diester monomer M4: 9.614 with a yield of 85.15%.
[0039] Under nitrogen protection, 6.775g (0.012mol) of diester monomer M4, 2.203g (0.011mol) of dimethyl 1,4-cyclohexanedicarboxylate, and 1.802g (0.02mol) of ethylene glycol dihydroxymethyl ether were added to a reaction vessel, and 0.0068g of potassium fluorotitanate (IV) was added. The mixture was stirred and reacted for 2 hours at a temperature of 200°C and a N2 atmosphere. After that, the reaction system was controlled to have a vacuum degree of 130Pa and a temperature of 355°C for a polycondensation reaction for 1 hour to obtain a crude polyester. The crude polyester was dissolved in chloroform, the insoluble matter was filtered out, and sufficient methanol was added to the clear liquid until the precipitation no longer increased. The filtered precipitate was washed 3 times with cooled methanol, and the obtained solid was dried at 50°C for 1h after filtering again to obtain polyester P4: 9.216g, with a yield of 88.50%.
[0040] The polyester P4 obtained by the preparation method of the polyester based on coumestrol is used as the base material for preparing the insulating heat-resistant material. The preparation method comprises the following steps: 92 parts by mass of the polyester P4 based on coumestrol, 5 parts by mass of nano-SiO2 with a particle size of 100 nm, 1 part by mass of the antioxidant JY-626 and 2 parts by mass of the polycarbodiimide anti-hydrolysis agent are put into a high-mixer for uniform blending, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material. The polyester composite material is processed into a 45 μm polyester composite material by a blow molding process, and the electrical insulation performance, heat resistance, mechanical properties and thermal stability of the polyester composite material are tested (the results are shown in Tables 1 and 2 below). The prepared polyester composite material can be used for the protection of electronic component housings.
[0041] Example 5.
[0042] Synthesis of diester monomer M5: Under N2 protection, 5.364g (0.02mol) of coumestrol and 9.896g (0.0432mol) of methyl 3-bromomethylbenzoate were added to a 100mL round-bottom flask, and 30mL of N,N-dimethylformamide was added as the reaction solvent. The mixture was stirred with a magnetic stirrer to dissolve it. Then, 2.985g of potassium carbonate was added. The reaction mixture was heated to 85°C and stirred for 2 hours. The filtered solid was washed with distilled water until it was neutral, recrystallized with chloroform, and dried in an oven at 50°C for 2 h to obtain diester monomer M5: 9.697g, with a yield of 85.88%.
[0043] Under nitrogen protection, 6.775g (0.012mol) of diester monomer M5, 2.203g (0.011mol) of dimethyl 1,4-cyclohexanedicarboxylate, and 1.983g (0.022mol) of ethylene glycol dihydroxymethyl ether were added to a reaction vessel, and 0.0136g of tin (II)-ethylhexanoate was added. The mixture was stirred at 210°C and N2 atmosphere for 2 hours, and then the vacuum degree of the reaction system was controlled to be 140Pa and the temperature was 350°C for polycondensation reaction for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform, the insoluble matter was filtered out, and sufficient methanol was added to the clear liquid until the precipitation no longer increased. The filtered precipitate was washed twice with cooled methanol, and the obtained solid was dried at 50°C for 2 hours after filtering again to obtain polyester P5: 9.405g, with a yield of 85.80%.
[0044] The polyester P5 obtained by the preparation method of the polyester based on coumestrol is used as the base material for preparing the insulating heat-resistant material. The preparation method comprises the following steps: 92 parts by weight of the polyester P5 based on coumestrol, 5 parts by weight of nano-SiO2 with a particle size of 100 nm, 1 part by weight of the antioxidant JY-626 and 2 parts by weight of the polycarbodiimide anti-hydrolysis agent are put into a high-mixer for uniform blending, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material. The polyester composite material is processed into a 50 μm polyester composite material by a blow molding process, and the electrical insulation performance, heat resistance, mechanical properties and thermal stability of the polyester composite material are tested (the results are shown in Tables 1 and 2 below). The prepared polyester composite material can be used for the shell of electronic component packaging materials.
[0045] Example 6.
[0046] Synthesis of diester monomer M6: Under N2 protection, 5.364g (0.02mol) of coumestrol and 10.079g (0.044mol) of methyl 3-bromomethylbenzoate were added to a 100mL round-bottom flask, and 30mL of N,N-dimethylformamide was added as the reaction solvent. The mixture was stirred with a magnetic stirrer to dissolve it. Then, 3.649g of potassium carbonate was added. The reaction mixture was heated to 90°C and stirred for 2 hours. The filtered solid was washed with distilled water until it was neutral. After recrystallization with chloroform, it was dried in an oven at 50°C for 1h to obtain diester monomer M6: 9.825g, with a yield of 87.02%.
[0047] Under nitrogen protection, 6.775g (0.012mol) of diester monomer M6, 2.203g (0.011mol) of dimethyl 1,4-cyclohexanedicarboxylate, and 2.163g (0.024mol) of ethylene glycol dihydroxymethyl ether were added to a reaction vessel, and 0.0203g of dibutyltin (II) oxide was added. The reaction was stirred at 220°C and N2 atmosphere for 2 hours, and then the vacuum degree of the reaction system was controlled to be 150Pa and the temperature was 345°C for polycondensation reaction for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform, the insoluble matter was filtered out, and sufficient methanol was added to the clear liquid until the precipitation no longer increased. The filtered precipitate was washed 3 times with cooled methanol, and the solid obtained was dried at 50°C for 2 hours after filtering again to obtain polyester P6: 9.857g, with a yield of 88.48%.
[0048] The polyester P6 obtained by the preparation method of the polyester based on coumestrol is used as the base material for preparing the insulating heat-resistant material. The preparation method comprises the following steps: 92 parts by mass of the polyester P6 based on coumestrol, 5 parts by mass of nano-SiO2 with a particle size of 100 nm, 1 part by mass of the antioxidant JY-626 and 2 parts by mass of the polycarbodiimide anti-hydrolysis agent are put into a high-mixer for uniform blending, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material. The polyester composite material is processed into a 50 μm polyester composite material by a blow molding process, and the electrical insulation performance, heat resistance, mechanical properties and thermal stability of the polyester composite material are tested (the results are shown in Tables 1 and 2 below). The prepared polyester composite material is used for wire and cable coating.
[0049] .
[0050] [4]Wang, JG; Zhang, XQ; Shen, A.; Zhu, J.; Song, PA; Wang,H.; Liu,
[0051] .
[0052] [5]ZHANG S, CHEN WJ, ZHAO YS, et a1. Designing multi-aromatic ringepoxy composites to integrate high insulation and high heat resistanceperformances by electron-induced effect[J]Composites Part B: Engineering, 2022, 243: 1 10107. .
[0053] From the data comparison in Table 1, it can be seen that the present invention uses the diester monomer M, 1,4-cyclohexanedicarboxylic acid dimethyl ester and ethylene glycol dihydroxymethyl ether as raw materials to synthesize polyesters P1 to P6. The number average molecular weight of the coumestrol-based polyesters P1 to P6 prepared by the present invention is 6.7×10 4 ~7.8×10 4g / mol, and the molecular weight distribution coefficient PDI is 1.78~1.84. The polyesters P1~P6 prepared by the present invention are similar to those prepared by Wang, J. G [4] Compared with the reported polyester material PETH, the mechanical properties are improved, the tensile strength is 28.7~36.6MPa higher than that of PETH, the tensile modulus is 680~830 MPa higher than that of PETH, and the elongation at break is 90.6%~118.9% higher than that of PETH. It can be seen that the mechanical properties of the coumestrol-based polyester prepared by the present invention are greatly improved.
[0054] From the data comparison in Table 2, it can be seen that the glass transition temperature of the polyesters P1 to P6 based on coumestrol prepared in the present invention is 267.3 to 272.5°C, and the thermal decomposition temperature T d(10%) The melting point is 482~507℃, the melting point is 307.5~336.5℃, the breakdown strength is 64.62~65.48kV / mm, the dielectric constant is 2.4~2.7, and the dielectric loss is 0.0012~0.0017. [5] Compared with the reported high heat-resistant insulating composite materials, the glass transition temperature of the polyesters P1-P6 prepared by the present invention is increased by 32.8-38.0°C, and the thermal decomposition temperature T d(10%) The temperature was increased to 85.4-110.4°C, the breakdown strength was increased to 25.44-26.32 kV / mm, the dielectric constant was reduced by 0.67-0.97, and the dielectric loss was reduced by 0.0018-0.0023. The insulation performance and heat resistance of the prepared coumestrol-based polyester of the present invention are further improved.
[0055] The polyester P based on coumestrol prepared by synthesizing the diester monomer M prepared by using coumestrol as raw material and 1,4-dimethyl cyclohexanedicarboxylate and ethylene glycol dihydroxymethyl ether has high molecular weight, good mechanical properties and thermal stability. The composite material based on the polyester of coumestrol shows excellent heat resistance and insulation, and its mechanical properties and thermal stability can also meet the application requirements, and can be used to prepare insulating heat-resistant materials, which are applied to industries such as electrical, electronic, and communication. Such as sheath materials for communication cables and optical cables, packaging materials for electronic components, insulating layers in electrical equipment, and insulating materials for electronic and electrical components. In summary, the present invention applies for the invention patent of "preparation and application of polyester and insulating heat-resistant materials based on coumestrol", and the insulating heat-resistant composite material based on coumestrol polyester will have good market application prospects.
[0056] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. Coumestrol-based polyester P, characterized in that The structure is as shown in Formula Ⅰ: Wherein: in formula Ⅰ, m is 50~60, and n is 62~78.
2. A method for preparing a polyester P based on coumestrol, characterized in that The preparation comprises the following steps: (1) Synthesis of diester monomer M: Synthesis of diester monomer M: 3,9-dihydroxy-6H-benzofuran (3,2-c) furan-6-one with CAS No. 479-13-0 and 3-bromomethylbenzoic acid methyl ester are added into a reactor at a molar ratio of 1: (2-2.2), N,N-dimethylformamide is added under stirring to dissolve it, and then potassium carbonate of 0.5-0.6 times the molar amount of 3-bromomethylbenzoic acid methyl ester is added, and then the reaction mixture is heated to 80-90°C, and the reaction is continued with stirring for 1-3 hours. The filtered solid is washed with distilled water until it is neutral, recrystallized with chloroform, and dried in an oven at 50°C for 1-2 hours to obtain a diester monomer M, the structure of which is as shown in Formula II: (2) Preparation of polyester P based on coumestrol: 1) Synthesis of polyester crude product: Under nitrogen protection, the structure of the polyester prepared in (1) is The diester monomer M, 1,4-cyclohexanedicarboxylic acid dimethyl ester with CAS number 94-60-0, and ethylene glycol dihydroxymethyl ether with CAS number 3586-55-8 are added into a reactor in a certain proportion, a certain amount of catalyst is added, and the mixture is stirred and reacted at a temperature of 200-220° C. and N2 atmosphere for 2 hours, and then the vacuum degree of the reaction system is controlled at 100-150 Pa and the temperature is 340-355° C. to carry out polycondensation reaction for 1-2 hours to obtain a crude polyester product; 2) Purification of polyester: dissolve the crude polyester with chloroform, filter out the insoluble matter, add methanol to the clear liquid until the precipitate no longer increases, wash the filtered precipitate with cooled methanol 2 to 3 times, filter again and dry the obtained solid at 50°C for 1 to 2 hours to obtain the desired coumestrol-based polyester P.
3. The preparation of the coumestrol-based polyester P according to claim 2, characterized in that: The catalyst in step (2) is one of tin (II)-ethylhexanoate, dibutyltin (II) oxide, titanium (IV) isopropanol, and potassium fluorotitanate (IV). The amount of the catalyst used is 0.1% to 0.3% of the mass of the diester monomer M in (1).
4. The method for preparing the coumestrol-based polyester P according to claim 2, characterized in that: In step (2), the molar ratio of the diester monomer M to dimethyl 1,4-cyclohexanedicarboxylate and ethylene glycol dihydroxymethyl ether is 1.2:(1-1.1):(2.0-2.4).
5. The polyester P obtained by the method for preparing the polyester based on coumestrol as described in claim 2 is used as a base material for preparing insulating heat-resistant materials, and the preparation method comprises the following steps: 92 parts by mass of the polyester based on coumestrol prepared as described in claim 2, 5 parts by mass of nano-SiO2 with a particle size of 100 nm, 1 part by mass of antioxidant 626 and 2 parts by mass of polycarbodiimide anti-hydrolysis agent are put into a high-speed mixer or a plastic high-speed mixer and blended evenly, and then extruded and granulated by an extrusion granulator to obtain the base material for preparing the insulating heat-resistant material.